Criterios para la evaluación de tesis doctorales - Martínez Montalvo, Esperanza; López Yepes, José; Orera Orera, Luisa; Sánchez Vigil, Juan Miguel; Hernández Pacheco, Federico; Prat Sedeño, Judit; Fernández Bajón, María Teresa; Sánchez, Carlos Manuel (Revista General de Información y Documentación, 2009)
In this paper, we propose a questionnaire directed at accurately assessing the quality of doctoral dissertations in its different stages, both a-priori, in the doctoral defence, and a-posteriori, whenever the dissertation be newly assessed as part of an application for a research grant, prize, etc. These criteria are independent of a further assessment of the dissertation as a published text.
Keywords: Doctoral Dissertations; Assessment of Doctoral Dissertations